Methods to determine scientific publications citation of a researcher - K. S. Borgoyakova (Библиосфера)
The article represents two methods of estimating publication citations based on information-analytical systems «Map of Russian science» (IAS MRS) using analytical tools of this system to evaluate research significance of scientists. These techniques are advisory in nature and exemplified by two researchers, who publish the most actively in journal «Scientific and Technical Libraries». They can only be used for the analysis of citation of verified scientists in IAS MRS. The paper gives a comparison with the IAS Russian Science Citation Index. The advantage of the first technique is obtaining data to study the researcher profile in detail. The bibliometric analysis of an individual approach, in contrast to the comparative approach of the second technique is not directed to get the characteristics of «more, less, equal», but to study bibliographic information about publications obtaining not quantitative but qualitative data.The comparative-analytical method has a statistical character showing a quantitative picture, which is the information basis for further bibliometric analysis and getting new qualitative results.